Upaya Menurunkan Kadar Ion Logam Besi Pada Air Sumur Dengan Memanfaatkan Arang Ampas Tebu - Dahlia Rosma Indah; Hendrawani Hendrawani (Universitas Pendidikan Mandalika Mataram, 2019)
The levels of iron metal ions in the well water can cause health problems,causing the yellow color on the walls of the bathroom tub and the yellowspots on the clothes. One way of water treatment is by adsorption techniqueusing charcoal from bagasse. The first step is to first determine the level ofiron metal ions in the well water in the village of Palempat, BatulayarDistrict, West Lombok. Furthermore, the well water is contacted with sugarcane bagasse. The manufacture of amphibians includes the samplepreparation process, wash with water, drying in the sun, and the refining at250ºC for 2.5 hours then sieved. The sugarcane bagasse that has been putinto 100mLsampelair well with a mass of 2 grams of adsorbent. Samples werethen stirred at contact time variations of 30, 60, 90, 120 and 150 minutes at180 rpm using a batch system. The best contact time used to calculate theefficiency of decreasing iron metal ion content is by calculating the differenceof iron metal ions before adsorption and after adsorption using charcoal ofbagasse. From the research, it was found that iron metal ion content in thesample was 0.1683 ppm. The optimum contact time on iron metal ionadsorption is at 120 minutes contact resulting in optimum adsorptionefficiency in iron metal that is 65.83%.